The effect of self-control and financial literacy on impulsive borrowing: Experimental evidence - Antonia Grohmann; Jana S. Hamdan (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This paper examines the effect of reduced self-control on impulsive borrowing in a laboratory experiment. We manipulate self-control using an ego depletion task and show that it is effective. Following the ego depletion task, participants can anonymously buy hot drinks on credit. We find no significant average effects, but find that treated individuals that have low financial literacy are more likely to borrow impulsively. We complement our experimental analysis with survey evidence that suggests that people with low self-control have more problems with the repayment of consumer debt. This relationship is, in line with the experimental results, weaker for individuals with high financial literacy.
Keywords: D14; G51; C91; 330; Debt; Consumption; Borrowing; Self-Control; Ego depletion